Law Enforcement And Factors Background To The Crime Of Fraud In Online Selling Transactions In Indonesia - Apriyas Munik; Fajar Ali Syabana; Ewin Eka ijayanto Wijayanto; Ali Rasya; Sufiarina Sufiarina (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2023)
The country of Indonesia is experiencing the growth of online shops which are developing very rapidly, several electronic transaction sites (e-commerce) or commonly called online shops which are well known especially to the people in Indonesia, including: Bukalapak.com, Tokopedia, OLX, Blibli.com, Elevenia, Lazada, Shopee, Berrybenka, Blanja.com, Zalora, JD.id and others. However, related to technological developments is one of the factors that can lead to crime. The forms of crime that exist are increasingly varied and more contemporary. Crime has been accepted as a fact, both in the simplest (primitive) society and in modern society, which is detrimental to society. The losses incurred can be in the form of losses in the sense of material or immaterial. Material losses, for example victims of crime and damage or destruction of property as well as the increased costs that must be incurred for handling it. Immaterial losses can reduce or lose public trust in the implementation of law enforcement carried out by law enforcers. With the development of technology, in reality crimes through the misuse of information technology are increasingly being committed. The type and mode of crime itself continues to grow. Criminal acts of fraud in online buying and selling transactions are currently growing with the times and technological advances. Legal regulations are made to anticipate this, but the existing regulations do not seem to reduce these crimes but have increased. Based on what has been described in the background above, the author tries to identify the following problems: What are the legal provisions against perpetrators of fraud in online buying and selling transactions? What are the factors behind the crime of fraud in online buying and selling transactions in Indonesia? In this journal the author uses a normative juridical approach, namely a method in which law is conceptualized as norms, rules, principles or dogmas. Legal provisions against perpetrators of criminal acts of fraud in online buying and selling transactions. As is known, the arrangements regarding electronic transactions regulated in Law no. 11 of 2008 concerning Information and Electronic Transactions and Law no. 19 of 2016 concerning Amendments to Law no. 11 of 2008 concerning Electronic Information and Transactions as the main basis for online buying and selling arrangements and Government Regulation Number 71 of 2019 concerning Electronic System and Transaction Operations. .